Complicaciones en el parto y el puerperio entre las gestantes de una población española que están expuestas a la violencia de género - María Analía Gómez-Fernández; Iris Parra-Vega; Osval Corral-Vazquez (Universitat de Barcelona, 2023)
Objective. To explore whether exposure to gender-based violence (GBV) during pregnancy in a Spanish community is related to birth complications involving cesarean delivery or to puerperium complications. Methodology. Observational, descriptive and prospective study carried out in two public centers in L'Hospitalet de Llobregat (Barcelona). The pregnant women, assisted by midwives of the participating centers, completed the validated questionnaire for the detection of GBV Index of Spouse Abuse. Sociodemographic and obstetric variables were also collected. A descriptive, bivariate and multivariate analysis of the data was performed. Results. A sample of 381 pregnant women was obtained. The prevalence of psychological GBV was 7.35%, physical GBV was 3.67% and some form of violence was 8.92%. Exposure to psychological GBV or some form of violence significantly increased complications during labor (p=0.031 and p=0.025, respectively). Similarly, exposure to physical GBV increases the risk of puerperium complications (p=0.024). However, exposure to some form of GV was not associated after adjusting for other explanatory factors with delivery by cesarean section (OR=1; CI=0.29-3.03; p=0.994). Conclusions. Exposure to VG increases complications during labor and puerperium. Therefore, early detection of GV during pregnancy is critical to provide women with additional support and available resources so that this can have a positive impact on birth outcomes.